Pengaruh Literasi Keuangan, Bias Herding, Bias Keterwakilan, dan Locus of Control Terhadap Keputusan Investasi Seluruh Mahasiswa di Kota Surabaya - Karimah, Naura Firdausi; Condro Widodo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze and examine the influence of financial literacy, herding bias, representativeness bias, and locus of control on the investment decisions of all students in Surabaya. This research uses a quantitive approach. The study was conducted on 129 active studet respondents in Surabaya. The data analysis technique used in this study is the Structural Equation Model-Partial Least Square (SEM-PLS) approach with SmartPLS4.0. The data source used in this study is primary data from questionnaires distributed to respondents. Based on the test results conducted, this study shows that financial literacy has a significant positive effect on investment decisions, herding bias has a significant positive effect on investment decisions, representativeness bias has a significant positive effect on investment decisions, and locus of control has a significant positive effect on investment decisions.